Shape Design and Support Scheme of Roadways in Stratified Rock Masses: Based on Numerical Experiments and Field Case Studies - Dexian Li; Pengqiang Zhang; Yuanjun Sun; Baohui Tan; Telin Zeng; Yingpeng Hu; Mingrun Li; Fengyu Ren (Advances in Civil Engineering)
The deformation and failure characteristics of roadways in stratified rock masses are heavily influenced by the dip angle of the rock layers. Therefore, it is crucial to select an appropriate cross-sectional shape and support scheme to ensure roadway stability. This study utilizes a discrete element numerical simulation method to systematically investigate the failure modes of roadways in stratified rock masses under varying dip angles. The theory of pressure balance arches is integrated to establish optimal principles for determining the cross-sectional shape, and corresponding support schemes are proposed for roadways in stratified rock masses. The results indicate that as the dip angle of the rock layers changes, different failure modes occur, ranging from symmetric arch-shaped collapse to asymmetric wedge-shaped collapse and overall sliding failure. Based on the self-stabilizing properties of roadways under pressure balance arches, a straight-sidewalls and arch-roof cross-section is recommended for roadways with arch-shaped or overall sliding failures in their roofs, and a pentagonal cross-section is recommended for roadways with wedge-shaped collapses. The support parameters determined by well-established empirical criteria are generally applicable to roadways with arch-shaped or wedge-shaped roof failures. However, caution should be exercised when applying these parameters to roadways with overall sliding instabilities, as they may result in insufficient design robustness. Finally, a field case study of a copper mine in Zambia is presented to demonstrate the process of recommending appropriate roadway cross-sectional shape and support scheme.